2019
DOI: 10.25077/jijcs.1.2.8-15.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shallot Bulbs Storage Duration and Paclobutrazol Treatments to Disease Attacks on Shallot Plant in Karo Highlands

Abstract: A major challenge in the development of shallot seeds is the limited availability of qualified seed due to pathogen infection during the vegetative phase. The study aims to determine the effect of storage duration and paclobutrazol (PBZ) treatment to the resistance of shallots crop. The study was conducted at the Berastagi Experimental Fields, Vegetable Crops Research Institute in February to May 2017. The experiment was arranged by randomized block design with two factors. The first factor is bulbs storage du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The consequence of bulbs not having enough shelf life is that they cannot grow and are susceptible to soilborne pathogenic diseases that travel through the bulbs. Tarigan et al (2019) stated that ready-to-use shallot bulbs had been stored for at least 2 to 4 months, depending on the variety. This study also revealed that bulbs without a storage period were more susceptible to pathogens such as Peronospora destructor and Fusarium oxysporum.…”
Section: Percentage Of Rooted and Sprouted Bulbsmentioning
confidence: 99%
“…The consequence of bulbs not having enough shelf life is that they cannot grow and are susceptible to soilborne pathogenic diseases that travel through the bulbs. Tarigan et al (2019) stated that ready-to-use shallot bulbs had been stored for at least 2 to 4 months, depending on the variety. This study also revealed that bulbs without a storage period were more susceptible to pathogens such as Peronospora destructor and Fusarium oxysporum.…”
Section: Percentage Of Rooted and Sprouted Bulbsmentioning
confidence: 99%